Pemuridan dalam Perspektif 2 Timotius 2:2: Upaya Membangun Disiplin Rohani - Paulus Kunto Baskoro; David Pattinama; Endah Totok Budiono; Riston Batubara (Philoxenia: Jurnal Teologi dan Pendidikan Kristiani, 2022)
Discipleship is an important part of the Person of the Lord Jesus, as long as he is on earth. Jesus has an important purpose in coming to this world, shich is to atone for the sins of manking and provide restoration of life for humans who should go to hell, when they believe in the Lord Jesus, they can enjoy heaven. But Jesus did not escape a discipleship that was carried out with the twelve disciples He had chosen. Jesus took a discipleship seriously for three and a half years. The church must also consistently carry out discipleship. Because through discipleship, spiritual discipline will accur effectively. Because it in undeniable, when the church is separated from the discipleship system, it will lose many generations and the church growth will be ineffective. The book of 2 Timothy 2:2 becomes an important text to explore the principle of discipleship that leads to spiritual discipline. The method used a descriptive method of literature. Thus research will discuss about effective ways of evangelism, so that evangelism is more effective and can be applied in all ages. The purpose of thus paper is First, to explain how important discipleship is. Second, examine the important prinsiples of discipleship fot the spiritual discipline of the church based on 2 Timothy 2:2. Third, apply the right discipleship system that can have an impact on today’s congregations.